Policy reforms and unresolved educational challenges in Ethiopia: Implications for the University of Education - Tena, Berhanemeskel; Motuma, Fisseha (Bahir Dar Journal of Education, 2024)
The purpose of this study was to examine the education reform initiatives and ongoing educational challenges in Ethiopia, with a focus on the role of the country's university of education in addressing these challenges. Using a qualitative research approach, the study examined reform documents, research findings, and personal experiences as its primary sources of data. Additionally, semi-structured interviews were conducted with 12 senior university instructors who were selected purposively. The results of the study revealed that Ethiopia's education system has undergone multiple reform initiatives, resulting in some visible improvements. Despite this, the study highlighted numerous challenges that persist in the country’s education system. In light of this, the study emphasized the importance of evidence-based and innovative measures focusing on the quality, relevance, and efficiency agendas of education, mainly through the recently established university of education.